Mechanism of improving the stability of activated carbon catalyst by trace H2S impurities in natural gas for hydrogen production from methane decomposition. (1st September 2021) - Xuan, Guohui; Liu, Fang; Zhang, Fan; Hu, Yiling; Miao, Jinhan; Yang, Li
Graphical abstract: Highlights: The influence of H2 S on AC catalytic performance was studied. Trace H2 S is favored for AC-catalyzed methane decomposition. H2 S changes the morphology of deposited carbon. H2 S increases the number of micropores during AC inactivation. H2 S changes the path of methane decomposition. Abstract: Direct methane decomposition for hydrogen production is considered a clean technology with limited CO2 emission. However, catalysts usually suffer from deactivation due to carbon deposition. This study reported a method of improving the catalyst stability by using a trace amount of H2 S which naturally exists in natural gas, and the action mechanism of H2 S was discussed. Coconut shell activated carbon (AC) was used as the catalyst, the pure methane was mixed with 100, 200, and 300 ppm H2 S and decomposed at high temperature. Results show that adding different concentrations of H2 S can increase the methane conversion and delay the deactivation time of the AC catalyst. Through scanning electron microscopy characterization and Brunauer-Emmet-Teller analysis, it was found that the positive effect of H2 S is achieved by changing the carbon deposition morphology which in turn changes the AC pore width distribution and the specific surface area. Under the action of H2 S, AC has a relatively large number of micropores during the reaction, promoting the adsorption of methane molecules on AC. First-principles calculations show that H2 S changes the reaction pathway of methane dehydrogenation and promotes methane decomposition.